Modernist writing and reactionary politics - Ferrall, Charles (Cambridge University Press, 2001)
Ferrall argues that the politics of Yeats, Pound, Eliot, Lawrence, and Wyndham Lewis were a response to the separation of art from an increasingly industrialised society. Fascism became attractive to these writers because it promised to reintegrate art into society while simultaneously guaranteeing its autonomy.